Neurodegeneration: Keeping ATF4 on a Tight Leash - Pitale, Priyamvada M.; Gorbatyuk, Oleg; Gorbatyuk, Marina (Frontiers in Cellular Neuroscience, 2017)
Activation of the endoplasmic reticulum (ER) stress and ER stress response, also known as the unfolded protein response (UPR), is common to various degenerative disorders. Therefore, signaling components of the UPR are currently emerging as potential targets for intervention and treatment of human diseases. One UPR signaling member, activating transcription factor 4 (ATF4), has been found up-regulated in many pathological conditions, pointing to therapeutic potential in targeting its expression. In cells, ATF4 governs multiple signaling pathways, including autophagy, oxidative stress, inflammation, and translation, suggesting a multifaceted role of ATF4 in the progression of various pathologies. However, ATF4 has been shown to trigger both pro-survival and pro-death pathways, and this, perhaps, can explain the contradictory opinions in current literature regarding targeting ATF4 for clinical application. In this review, we summarized recent published studies from our labs and others that focus on the therapeutic potential of the strategy controlling ATF4 expression in different retinal and neurodegenerative disorders.